Enteric associated T-cell lymphoma in a mule - de Souza, Giovanna G [UNESP]; Lacerda, Zara A [UNESP]; de Moura, Fernanda B C [UNESP]; Contel, Isabeli J [UNESP]; de Oliveira, Shéron L [UNESP]; Ferrari, Lorena C [UNESP]; Apolonio, Emanuel V P [UNESP]; Alonso, Juliana de M [UNESP]; Alves, Ana Liz G [UNESP]; Rocha, Noeme S [UNESP] (Elsevier, 2024)
A 25-year-old female mule weighing 336 kg was referred with a history of lethargy, abdominal discomfort, anorexia, and constipation in the previous 24 hours. On admission, decreased intestinal borborygmi and distended small intestinal loops were detected by auscultation and rectal palpation, respectively. On rectal examination a firm, irregular surface, and pedunculated mass were detected in the middle-caudal region of the abdomen. Transrectal ultrasonography revealed the mass was highly vascularized with heterogeneous tissue density. On exploratory celiotomy two neoplastic masses were observed, one in the jejunoileal junction obstructing the intestinal flow and the second in the dorsal part of the jejunal mesentery, unable to be exposed and resected. An enterectomy was conducted, and the intestinal mass was removed. The mass was pale with hemorrhagic areas and 12 cm in diameter. Histopathology and immunohistochemistry confirmed a diagnosis of enteric associated T cell lymphoma subtype 2. The mule died suddenly 43 days later.